2020
DOI: 10.1182/bloodadvances.2020002524
|View full text |Cite|
|
Sign up to set email alerts
|

The immunomodulatory drugs lenalidomide and pomalidomide enhance the potency of AMG 701 in multiple myeloma preclinical models

Abstract: We investigated here the novel immunomodulation and anti–multiple myeloma (MM) function of T cells engaged by the bispecific T-cell engager molecule AMG 701, and further examined the impact of AMG 701 in combination with immunomodulatory drugs (IMiDs; lenalidomide and pomalidomide). AMG 701 potently induced T-cell–dependent cellular cytotoxicity (TDCC) against MM cells expressing B-cell maturation antigen, including autologous cells from patients with relapsed and refractory MM (RRMM) (half maximal effective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 68 publications
3
34
0
Order By: Relevance
“…Specifically, AMG 701 holds an extended half-life in vivo and mediates T-cell dependent cellular cytotoxicity (TDCC) of BCMA positive MM cells and is currently under clinical investigation (NCT03287908). We have also shown that MM cytotoxicity can be augmented at lower effector: tumor cell ratios when low doses of AMG 701 are combined with lenalidomide or pomalidomide, suggesting a favorable therapeutic index ( 70 ). Although early results look promising and both ADC and Bites approaches have the advantage for “off the shelf” availability, longer follow-up in larger studies is needed to assess their clinical efficacy and toxicity.…”
Section: Immunotherapy In MMmentioning
confidence: 87%
“…Specifically, AMG 701 holds an extended half-life in vivo and mediates T-cell dependent cellular cytotoxicity (TDCC) of BCMA positive MM cells and is currently under clinical investigation (NCT03287908). We have also shown that MM cytotoxicity can be augmented at lower effector: tumor cell ratios when low doses of AMG 701 are combined with lenalidomide or pomalidomide, suggesting a favorable therapeutic index ( 70 ). Although early results look promising and both ADC and Bites approaches have the advantage for “off the shelf” availability, longer follow-up in larger studies is needed to assess their clinical efficacy and toxicity.…”
Section: Immunotherapy In MMmentioning
confidence: 87%
“…The combination therapy with PD-1 blockers resulted in synthetic effects [ 109 ]. Immunomodulatory imide drugs including lenalidomide and pomalidomide could make AMG 701 more potent in xenograft models [ 110 ]. Phase I clinical trials of AMG 701 in patients with R/R MM are being conducted.…”
Section: Mechanisms Of Bite Actionmentioning
confidence: 99%
“…This BiTE has an extended half-life and has showed strong encouraging results [ 100 ]. A trial is currently recruiting RR MM patients to receive this therapy either as monotherapy or in combination with IMIDs (e.g., pomalidomide) and with or without dexamethasone (NCT03287908) [ 101 ]. BI 836909 is another T cell engager that has demonstrated successful in vivo anti-myeloma activity [ 102 ].…”
Section: Breakthrough Immune Therapies In MMmentioning
confidence: 99%